Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1080/20961790.2020.1869883
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the psychological aspects of the radicalisation process: a sociocognitive approach

Abstract: Understanding the psychological dimensions underlying the radicalisation process is a considerable challenge in the context of the legal judicial treatment of perpetrators of acts of radical violence. This clinical and qualitative study is based on an analysis of legal expert interviews of people at different stages of the radicalisation process. It highlights common psychological characteristics in personality, mechanisms of moral neutralisation and sociocognitive and interpretive treatment during radicalisat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…In 12.2% (N = 5) patients suffered from a psychotic disorder not otherwise specified [42,43,46,48] The final sample included ten studies, comprising observational studies (N = 5), case reports (N = 4) [42][43][44][45], and case series (N = 1) [46]. As regards study design, two were retrospective studies [41,47], one was a case-control study [32,37], one prospective longitudinal study [48], and one was a cross-sectional study [49]. Details on clinical studies are reported in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…In 12.2% (N = 5) patients suffered from a psychotic disorder not otherwise specified [42,43,46,48] The final sample included ten studies, comprising observational studies (N = 5), case reports (N = 4) [42][43][44][45], and case series (N = 1) [46]. As regards study design, two were retrospective studies [41,47], one was a case-control study [32,37], one prospective longitudinal study [48], and one was a cross-sectional study [49]. Details on clinical studies are reported in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…They engage in unrealistic thinking and might have problems with reality testing. Garcet (2021) investigated and found that the most prominent personality disorders reported were antisocial/dissocial and narcissistic both cluster B personality disorders. Campelo et al (2018) also found that personality disorders associated with terrorism were antisocial and histrionic traits; both were cluster B personality disorders, followed by obsessive, which was cluster A personality disorder.…”
Section: Boko Haram Terrorists On Interest Scalesmentioning
confidence: 99%
“…Out of 27 individuals who adhered to radical courses, 23 of them suffered personality disorders, with anti-social/dissocial being the most prominent, followed by narcissistic personality disorder. Further results showed that most suffered a double personality disorder diagnosis (Garcet, 2021). Campelo et al (2018) realized that personality disorders associated with terrorism were anti-social, obsessive, and histrionic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…General psychiatry is unprepared to confront this very unique phenomenon of radicalization. Garcet [ 5 ] has reported his direct experience with individuals in pre-trial detention who are suspected of terrorism. From these encounters, he developed a psychopathological model that provides a fuller understanding of the mechanisms of psychic functioning modification that are engaged during the radicalization process.…”
mentioning
confidence: 99%